PHARMACOKINETIC PARALLELS OF GENTAMICIN IN BLOOD, LYMPH NODES AND SOFT TISSUES OF A GUNSHOT WOUND TO AN EXTREMITY BY DIFFERENT METHODS OF ADMINISTRATION (Spectrum Journal of Innovation, Reforms and Development, 2023)
The widespread use of firearms with high kinetic energy in local military conflicts has led to an increase in the number of severe wounds to the extremities, characterized by significant damage to soft tissues, blood vessels and multiple fractures [4,6,10]. In the course of providing modern medical care to the wounded in Afghanistan and the Chechen Republic, it was found that in 28% of cases, gunshot wounds to the extremities were complicated by purulent-infectious processes [1,11,15]. At the end of the 20th century, both in the CIS countries and in the world as a whole, there was a sharp increase in the number of gunshot injuries among the civilian population [3,9]. Today, gunshot injury is an urgent problem not only for military medicine but also for civilian health care. The presence of inevitable bacterial contamination and massive destruction of tissues of modern gunshot wounds leads to a large number of purulent complications, which necessitates continuous improvement of local and general treatment methods [4]. A gunshot wound due to primary contamination, the presence of wound detritus, areas of soft tissue damage usually heals by secondary intention. In the event of primary microbial contamination of the wound, “street” strains, as well as saprophytes from the skin, enter it. The predominantly lymphomatous spread of the infection leads to the formation of abscesses near the wound, phlegmon, severe wound edema, and sepsis. In this regard, the methods of endolymphatic antibiotic therapy and stimulation of lymphatic drainage are of particular relevance [7,10].